Targeting communication interventions to decrease oncology family caregiver burden - Wittenberg-Lyles, Elaine (2012)
OBJECTIVES: The goal of this paper was to articulate and describe family communication patterns that give shape to four types of family caregivers: Manager, Carrier, Partner, and Loner. DATA SOURCES: Case studies of oncology family caregivers and hospice patients were selected from data collected as part of a larger, randomized controlled trial aimed at assessing family participation in interdisciplinary team meetings. CONCLUSION: Each caregiver type demonstrates essential communication traits with nurses and team members; an ability to recognize these caregiver types will facilitate targeted interventions to decrease family oncology caregiver burden. IMPLICATIONS FOR NURSING PRACTICE: By becoming familiar with caregiver types, oncology nurses will be better able to address family oncology caregiver burden and the conflicts arising from family communication challenges. With an understanding of family communication patterns and its impact on caregiver burden, nurses can aid patient, family, and team to best optimize all quality of life domains for patient as well as the lead family caregiver.